2013
DOI: 10.5812/cardiovascmed.13892
|View full text |Cite
|
Sign up to set email alerts
|

Heart ABCA1 and ppar- α genes expression responses in male rats: Effects of high intensity treadmill running training and aqueous extraction of black crataegus-pentaegyna

Abstract: Introduction:Heart as a high metabolic and aerobic tissue is consuming lipid as a fuel for its energy provision at rest during light and moderate exercise, except when lactate level is higher in blood circulation. It has been shown that any type of regular exercise and crataegus species would improve cardiovascular function and minimizes several risk factors via stimulating lipid metabolism by acting on enzymes and genes expression such as ABCA1 and PPAR α which are involving in this process.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
(30 reference statements)
1
20
1
Order By: Relevance
“…Irisin may modulate the PPARα signaling pathway, a key regulator of lipid metabolism that coordinates fat oxidation through a thermogenesis mechanism (5). Previous studies have reported an increase in PPARα following physical training (26,49,50). It seems practicable that endurance training and resistance training are beneficial in adipose metabolism by elevating the expression of FNDC5 and the subsequent increase in PPARα expression stimulation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Irisin may modulate the PPARα signaling pathway, a key regulator of lipid metabolism that coordinates fat oxidation through a thermogenesis mechanism (5). Previous studies have reported an increase in PPARα following physical training (26,49,50). It seems practicable that endurance training and resistance training are beneficial in adipose metabolism by elevating the expression of FNDC5 and the subsequent increase in PPARα expression stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…This solution was incubated at a temperature of 55 o C for 15 minutes and immediately subjected to -80 o C. Subsequently, by the means of a cDNA synthesis kit (BIONEER, Korea), cDNA was synthesized from the RNA. The nucleotide primer sequences of FNDC5 gene (25) and the reference gene (26) are given in Table 1. Real Time PCR was run to measure the level of gene expression and was programmed with an initial step of 5 mins at 95ºC (1 cycle), followed by 40 cycles of 15 seconds at 95ºC and 30 seconds at 60º.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported different responses of PPAR α gene expression to different exercises (26)(27)(28)(29)40) (40). Iemitsu et al (2002) found that exercising improves the induction of a decrease in PPAR α levels in the cardiac tissue of elderly mice (41).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have recently focused on the effects of PPARs activities on fat metabolism (24,25) and studied the relationship between physical activities and PPARs gene expression. However, most of these studies were carried out on healthy subjects (26,27) or animal models (28,29), and mainly examined aerobic exercises and reported different results (26,28,29). In one study, Chen et al (2014) reported a significant increase in PPAR-δ gene expression in skeletal muscles (vastus lateralis) after ten weeks of progressive resistance training in young men and women (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation